Surgery versus neoadjuvant chemoradiotherapy followed by surgery in locally advanced gastrointestinal tract cancers - Ye, Xuxing; Wu, Zhangqiang; Teng, Weijun; Zhang, Yili; Chen, Yanping; Sheng, Lin; Lin, Junmei; Wang, Xiaobo (Frontiers in Oncology, 2025)
BackgroundGastrointestinal tract cancer is still prevalent in the world. Localized GI cancer treatment has greatly relied on surgery, even for locally advanced diseases.Aim and objectivesThe goal of this study was to assess the prognosis of direct surgery and neoadjuvant chemoradiotherapy and surgery in patients with locally advanced GI tract cancers.Materials and methodsA cross-sectional study was done on patients diagnosed with locally advanced GI cancers who were treated at Zhejiang Jinhua Guangfu Cancer Hospital between the period Jan 2021 to December 2023, total number of patients was 245. Patients were divided into two cohorts: DS of 107 and CRS of 138. Disease-free survival was the main predictor, while the others were considered secondary endpoints; these were overall survival, pathological complete response rate, postoperative complications, and R0 resection rate.ResultsDisease-specific survival benefitted the CRS cohort relative to the DS cohort with a 2-year DFS of 76.81% compared to 65.42% (p= 0. 049). Median DFS also favored the CRS group (34. 7 months vs 28. 3 months, p = 0. 023). While not statistically significant, there was a trend towards improved OS in the CRS cohort (2-year OS rate: The results are as follows: 81. 16% versus 72. 90%, p=0.124. The CRS group had higher resection of R0 (92.8% vs 86.0%, p=0.082), and similarly, the local recurrence and distant metastases, although non-significant, were lower in this group.ConclusionLocally advanced GI tract cancer appears to be improved from neoadjuvant-applied chemoradiotherapy followed by surgery rather than upfront surgery. Whereas, the trend about OS was in favor of the CRS approach, perhaps more time is required to observe these differences. The multimodal technique had reasonable presurgical toxicities and did not worsen the rate of postoperative complications. These findings support the consideration of neoadjuvant chemoradiotherapy can be recommended as a viable treatment approach for locally advanced GI tract cancers but future comparative prospective trials must be conducted to determine long-term survivals and quality of life patterns.